Association between papillary thyroid cancer and XRCC6 gene polymorphisms in the Turkish population - AKGÜN, EGEMEN; MUTLU İÇDUYGU, FADİME; ŞENGÜL, DEMET; ALP, EBRU; ALKANAT, MEHMET; CEBİ, AYSEGÜL; OZTURK, TUNCER (Turkish journal of medical sciences, 2024)
To investigate the association between the rs2267437, rs5751129 and rs132770 polymorphisms of the gene, which plays a role in repairing DNA double-strand breaks, and the risk of papillary thyroid carcinoma (PTC). The study included 150 patients who had been diagnosed with PTC and 204 healthy controls. Genotyping of the SNPs was performed using polymerase chain reaction-restriction fragment length polymorphism (PCR-RFLP). In the rs2267437 polymorphism, individuals with the GG genotype had lower risk of PTC than those with the wild-type CC genotype (p = 0.037, 95% CI: 0.19-0.96, OR: 0.67). The combined genotypes CG+GG were related to a reduced risk of PTC compared to the wild-type CC genotype (p = 0.023, 95% CI: 0.40-0.94, OR: 0.61) in the recessive model (GC+GG vs. CC). In addition, a query of the genotype-tissue expression (GTEx) database showed that the rs2267437 polymorphism may alter the expression level of in whole blood (p = 0.0009) but not in thyroid tissue. There were no significant associations between the rs5751129 and rs132770 polymorphisms and PTC. This study demonstrated that rs2267437 polymorphism may have a protective effect against PTC in the Turkish population. However, the rs5751129 and rs132770 polymorphisms were not associated with the disease.